Batch and Fixed-Bed Modeling of Adsorption Reactive Remazol Yellow Dye onto Granular Activated Carbon (Journal of Engineering, 2014)
In this work, the adsorption of reactive yellow dye (Remazol yellow FG dye) by granular activated carbon (GAC) was investigated using batch and continuous process. The batch process involved determination the equilibrium isotherm curve either favorable or unfavorable by estimation relation between adsorption capacity and concentration of dye at different dosage of activated carbon. The results were fitted with equilibrium isotherm models Langmuir and Freundlich models with R2value (>0.97). Batch Kinetic study showed good fitting with pseudo second order model with R2 (0.987) at contact time 5 h. which provesthat the adsorption is chemisorptions nature. Continuous study was done by fixed bed column where breakthrough time was increased at flow rates (21.67, 12.5 and 6 ml/min) and initial dye concentration (80, 40, 20 and 10 mg/l) were decreased and bed depth was increased (5, 10, 15 and 20 cm). The adsorption data were fitted to the fixed-bed adsorption mathematical models Thomas and Yoon- Nelson models. The results fitted well to the Thomas and Yoon-Nelson models with correlation coefficient, R2≥ 0.944. Average relative error ARE% was applied to examine the theoretical and experimental results.